ESTIMATION OF HERITABILITY AND SELECTION RESPONSE FOR BODY LENGTH OF NEON TETRA (Paracheirodon innesi) FROM BOJONGSARI DISTRICT, INDONESIA - Siti Zuhriyyah Musthofa; Alimuddin Alimuddin; Harton Arfah; Dinar Tri Soelistyowati; Odang Carman; Eni Kusrini (Indonesian Aquaculture Journal, 2026)
The neon tetra (Paracheirodon innesi), a popular South American ornamental fish, has become a key species in Indonesian aquaculture, with production centered in Bojongsari, Depok. However, the industry faces declining genetic quality due to inbreeding. Therefore, implementing a selective breeding program is considered an effective approach to improve genetic quality. This study aimed to estimate the heritability and selection response of the body length trait in the base population of neon tetra fish. Selection was conducted on the entire population using a within-family selection method, specifically employing broodstock from the Curug and Bojongsari populations. A reciprocal breeding design was established using four mating combinations, each comprising 25 pairs of 4- to 5-month-old broodstock (3.28±0.15 cm total length; 0.43±0.06 g body weight) mated at a 1:1 sex ratio. The offspring were reared separately and grown out in an aquarium for 120 days. The results showed that the estimated heritability was 0.42, with a response to selection of 0.13 cm (4.9%). Our finding of moderate heritability implies that this trait can be effectively enhanced through a systematic breeding program. These figures suggest that the selection process for the next generation of neon tetra fish remains viable.